STRATEGI PENDIDIKAN KARAKTER MUKMIN DI M. TON/M. PLAI SEKOLAH ISLAM SARTMULNITI PHATTALUNG THAILAND - Maisu, Mr. Anat (Profetika Jurnal Studi Islam, 2017)
The strategies used for mu’min character education in high school of Islamsart foundation school located at Phattalung province in Thailand in the academic year 2017/2018. The purpose of this research is to describe the implementation of mu’min character education, describes the methods used for mu’min character education, and to find the supporting factors and the thwarting factors faced within the process of implementing mu’min charcter education in high school of Islamsart foundation school located at Phattalung province in Thailand in the academic year 2017/2018. This research is a qualitative research based on a field research study with ethnographic approach. The location of that research is high school of Islamsart foundation school located at Phattalung province in Thailand. Technique of collecting data in that research is based on interviews, observation, and documentation. Analysis is done on that research by collecting data, reduction of data, displaying data, and conclusion. The results of this research regarding the implementation of mu’min character education in high school of Islamsart foundation school located at Phattalung province in Thailand in the academic year 2017/2018 can be explained as follows: takwa, mahabbatullah, muraqabah, ikhlas, tawakkal, shukur, taubat, loving and glorifying the prophet SAW, following and obeying the prophet SAW, saying shalawat and salam to the prohet SAW, Birrulwalidain, obeying leaders, visiting people, hospitability, having good relations with neighbors, and islam brothers and sisters, to be just and fair, to follow the amar ma’ruf nahi munkar rules, shiddiq, amanah, istiqamah, tawadhu, shy, patient, forgiving, generous, and to make use of the nature according to your needs and still work on preserving it. The method used in mu’min character education in high school of Islamsart foundation school located at Phattalung province in Thailand in the academic year 2017/2018 is as follows: giving commands and prohibitions, holding dialogues, targhib wa tarhib, stories, habituation, and setting some exemplary models. Supporting factors are: the role of sheikh and the headmaster, curriculum, school atmosphere, and school surroundings. The thwarting factors are: the big number of students and the quality of students' understanding of Islam.Strategi pendidikan karakter mukmin di M. ton/M. plai sekolah Islamsartmulniti provinsi Phattalung, Thailand pada tahun pelajaran 2017/2018. Tujuan penelitian ini adalah: Untuk mendeskripsikan implementasi karakter mukmin, dan mendeskripsikan metode yang digunakan dalam mendidik karakter mukmin, serta menemukan faktor pendukung dan penghambat pendidikan karakter mukmin di M. ton/M. plai sekolah Islam sartmulniti provinsi Phattalung, Thailand pada tahun pelajaran 2017/2018. Penelitian ini adalah penelitian kualitatif yang berjenis penelitian lapangan dengan pendekatan etnografi. Lokasi penelitian di M. ton/M. plai sekolah Islam sartmulniti provinsi Phattalung, Thailand. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian tentang karakter mukmin yang diimplementasikan di M. ton/M. plai sekolah Islamsartmulniti provinsi Phattalung Thailand  pada tahun pelajaran 2017/2018 adalah sebagai berikut: takwa, mahabbatullah, muraqabah,  ikhlas, tawakkal, syukur, taubat, mencintai dan memuliakan Rasulullah Saw, mengikuti dan menaati Rasulullah Saw, mengucapkan shalawat dan salam untuk Rasulullah Saw, Birrulwalidain, Menaati pemimpin, Bertamu,  Menerima tamu, hubungan baik dengan tetangga, ukhuwah islamiyah, adil, amar makruf nahi munkar, shiddiq, amanah, istiqamah, tawadhu, malu, sabar, pemaaf, pemurah, memanfaatkan alam sesuai kebutuhan dan menjaga lingkungan. Metode yang digunakan dalam mendidik karakter mukmin di M. ton/M. plai sekolah Islamsartmulniti provinsi Phattalung Thailand pada tahun pelajaran 2017/2018 adalah sebagai berikut: perintah dan larangan, dialog, targhib wa tarhib, kisah, pembiasaan, dan keteladanan. Faktor pendukung adalah: peran kiyai dan kepala sekolah, kurikulum, lingkungan sekolah, dan lingkungan sekitar sekolah. Faktor penghambat adalah: jumlah siswa yang begitu  banyak, dan kualitas pemahaman Islam para siswa.